A Comparative Study of Experimental and Theoretical Ultrasonic Velocity of Binary Liquid Mixtures Using Mathematical Methods - Gayathri, A.; Venugopal, T.; Venkatramanan, K. (International Journal of Engineering and Technology, 2018)
A comparative study of ultrasonic velocities of binary liquid mixtures such as O-cresol+carbon tetrachloride, anisicaldehyde+methylacetate, anisicaldehyde+ethylacetate, having industrial applications are analysed at temperature 303K for different concentrations [0 to 1%]. In the present study experimental values are taken from literature and there values are compared with theoretical values obtained by various mathematical equations such as Nomoto’s relation, VandealVangeal formula, Impedance relation, Rao’s specific relation. Thus, the present study reveals the nature of interaction between component molecules in the mixtures and enables us to identify a suitable mathematical model for predicting the ultrasonic velocity various binary liquid mixtures.